Fecal microbiota transplantation in a child with severe ASD comorbidities of gastrointestinal dysfunctions—a case report - Hu, Cong; He, Tianyi; Zou, Biao; Li, Heli; Zhao, Jinzhu; Hu, Chen; Cui, Jinru; Huang, Zhihua; Shu, Sainan; Hao, Yan (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder defined by social communication impairments and restricted, repetitive behaviors. In addition to behavioral interventions and psychotherapies, and pharmacological interventions, in-depth studies of intestinal microbiota in ASD has a obvious abnormalities which may effectively influenced in ASD. Several attempts have been made to indicated that microbiota can reduce the occurrence of ASD effectively. Fecal microbiota transplantation (FMT) is a type of biological therapy that involves the transplant of intestinal microbiota from healthy donors into the patient's gastrointestinal tract to improve the gut microenvironment. In this case report, we describe a case of child ASD treated by FMT. The patient have poor response to long-term behavioral interventions. After five rounds of FMT, clinical core symptoms of ASD and gastrointestinal(GI) symptoms were significantly altered. Moreover, the multiple levels of functional development of child were also significantly ameliorated. We found that FMT changed the composition of the intestinal microbiota as well as the metabolites, intestinal inflammatory manifestations, and these changes were consistent with the patient's symptoms. This report suggests further FMT studies in ASD could be worth pursuing, and more studies are needed to validate the effectiveness of FMT in ASD and its mechanisms.